Present Status and Challenges on Agricultural Microbe Bio-Prospecting in Indonesia - Sukara, Endang (ANNALES BOGORIENSES, 2007)
food security is  one of the essential needs which can never be  ignored by any society,  including in particular Indonesia. as the world population is expected to rise to around  10 billion marked by 2025. The problem  is that the agriculture in developed and developing countries that  follow the path of developed countries experiences create · a  range of  serious environmental degradation. An  intensive agricultural production through the use of pesticide and herbicides, forest clearing and continued use of land resources  for the agricultural purposes are not sustainable practice  .  In  consequences,  degradation  of ecosystem,  oil  erosion.  and  low  productivity  of land,  poor water quality and lost of biological  diversity  (including microbial  and  genetic  resources) occurred  at alarming  stale. Meanwhile,  the efforts  in  addressing  the above  situation  is  traditionally  focused on plant phenotypes (breeding. plant genetic engineering etc .) but the important role of microbial communities that interact with plants to influence plant health and productivity has been  largely ignored. The  interaction of microbes with plants and  its  relevant to soil  fertility and productivity, the bio-control properties of microbes and challenges toward sustainable agriculture is highlighted.